Ṭalīʻah-'i inqilāb-i Islāmī : muṣaḥabah'hā-yi Imām Khumaynī dar Najaf, Pārīs va Qum - Khomeini, Ruhollah (Markaz-i Nashr-i Dānishgāhī (Series), 1983)
(On political conditions in Iran on the eve of the 1979 Islamic revolution; press, radio, and television interviews)